Peripheral blood cell anomalies in COVID-19 patients in the United Arab Emirates: A single-centered study - Elemam, Noha Mousaad; Talaat, Iman M.; Bayoumi, Fatehia A.; Zein, Dima; Georgy, Ramy; Altamimi, Abdalrahman; Alkhayyal, Noura; Habbal, Alaa; Al Ali, Feda; ElKhider, Alaa; Ahmed, Abdallah; Abusnana, Salah; et al. (Frontiers in Medicine, 2022)
In this study, we aimed at exploring the morphologic and quantitative abnormalities in the peripheral blood counts of COVID-19 patients. A cohort of 131 COVID-19 patients was recruited at University Hospital Sharjah (UHS), UAE. Their peripheral blood smears were examined for morphological evaluation. Also, their clinical laboratory investigations and radiological findings were retrieved from the medical records. Our cohort consisted of 63 males and 68 females with an age of 63.6 ± 18.6 years. The presence of atypical lymphocytes was observed in around 80% of the recruited COVID-19 patients. Further, monocytes with toxic cytoplasmic vacuoles were identified in 55% of the cases. Neutrophil-associated changes, including pseudo-Pelger-Huët, bands, and long nuclear endoplasm, were reported in around 25-35% of the patients. RBCs associated changes such as microcytic and hypochromic RBCs, as well as targetoid, dacrocytes, ovalocytes, echinocytes/burr cells, and schistocytes, were described. According to disease severity, RBCs chromicity was found to be significantly different between stable and critical patients. COVID-19 patients with CO-RADS 5 showed a similar change in RBCs as well as a decrease in the neutrophils with hypogranular cytoplasm. In conclusion, peripheral blood smear assessment in COVID-19 patients could provide information about the disease state and pulmonary involvement.